Purification of Biodiesel Polluted by Copper Using an Activated Carbon Prepared from Spent Coffee Grounds: Adsorption Property Tailoring, Batch and Packed-Bed Studies - Daniel Eduardo Cárdenas-Piñeros; Hilda Elizabeth Reynel-Ávila; Lizbeth Liliana Díaz-Muñoz; Adrián Bonilla-Petriciolet; Carlos Javier Durán-Valle; Marta Adame-Pereira (Molecules)
Biodiesel produced via oil transesterification often contains metallic impurities, such as copper, which affects its quality and engine performance. This study explores the use of activated carbon prepared from spent coffee grounds to remove copper from biodiesel. Activated carbon samples were prepared via biomass pyrolysis and chemical activation with KOH and HNO3. The optimal conditions for copper adsorption were determined using a Taguchi L9 design. Maximum adsorption capacities were 13.4 and 17.3 mg/g at 30 and 40 °C, respectively, in batch adsorbers. In packed-bed columns, the axial dispersion reduced the adsorption efficiency obtaining bed adsorption capacities from 1.9 to 5.1 mg/g under tested experimental conditions. Adsorbent characterization and adsorption modeling indicated that copper removal was driven by multi-cationic interactions, where carboxylic groups from carbon surface acted as key active sites. The new adsorbent outperformed commercial bone char, making it a cost-effective alternative to improve biodiesel production contributing to the energy matrix diversification.